Production of exopolysaccharide from rhizobia with potential biotechnological and bioremediation applications - Luque Castellane, Tereza Cristina [UNESP]; Persona, Michelli Romanoli [UNESP]; Campanharo, Joao Carlos [UNESP]; Macedo Lemos, Eliana Gertrudes de [UNESP] (Elsevier B.V., 2015)
The potential use of rhizobia under controlled fermentation conditions may result in the production of new extracellular polymeric substances (EPS) having novel and superior properties that will open up new areas of industrial applications and thus increase their demand. The production of EPS and the stability of emulsions formed with soybean oil, diesel oil and toluene using different concentrations of purified EPS derived from wild-type and mutant strains of Rhizobium tropici SEMIA 4077 was investigated. The EPS was defined as a heteropolysaccharide composed of six constituent monosaccharides that displayed higher intrinsic viscosity and pseudoplastic non-Newtonian fluid behavior in an aqueous solution. The ratio between the total EPS production and the cellular biomass was 76.70 for the 4077:Z04 mutant strain and only 8.10 for the wild-type strain. The EPS produced by the wild-type R. tropici SEMIA 4077 resulted in more stable emulsions with the tested toluene than xanthan gum, and the emulsification indexes with hydrocarbons and soybean oil were higher than 50%, indicating strong emulsion-stabilizing capacity. These results demonstrate that the EPS of R. tropici strains could be attractive for use in industrial and environmental applications, as it had higher intrinsic viscosity and good emulsification activity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Bioemulsifier; Rhizobium tropici; Extracellular polysaccharides